Sex disparity and drug-induced liver injury. Issue 1 (January 2023) - Floreani, A.; Bizzaro, D.; Shalaby, S.; Taliani, G.; Burra, P.; ,
Abstract: Drug-induced liver injury (DILI) is a potentially serious clinical condition that remains a major problem for patients, physicians and those involved in the development of new drugs. Population and hospital-based studies have reported incidences of DILI varying from 1.4 to 19.1/100.000. Overall, females have a 1.5- to 1.7-fold greater risk of developing adverse drug reactions and the female/male ratio increases after the age of 49 years, suggesting a clear susceptibility of DILI after menopause. Sex differences in pharmacokinetics and pharmacodynamic, sex-specific hormonal effects or interaction with signalling molecules that can influence drug efficacy and safety and differences in abnormal immune response following drug exposure are the main probable causes of the higher vulnerability observed among female patients. A novel phenotype of autoimmune-mediated DILI following the use of check-point inhibitors in oncology and haematology has been recently described. Finally, there have been increasing reports of DILI associated with use of herbal and dietary supplements that is more frequently reported in women.